Casein Kinase II (CK2), Glycogen Synthase Kinase-3 (GSK-3) and Ikaros mediated regulation of leukemia. (August 2017) - Gowda, Chandrika; Soliman, Mario; Kapadia, Malika; Ding, Yali; Payne, Kimberly; Dovat, Sinisa
Abstract: Signaling networks that regulate cellular proliferation often involve complex interactions between several signaling pathways. In this manuscript we review the crosstalk between the Casein Kinase II (CK2) and Glycogen Synthase Kinase-3 (GSK-3) pathways that plays a critical role in the regulation of cellular proliferation in leukemia. Both CK2 and GSK-3 are potential targets for anti-leukemia treatment. Previously published data suggest that CK2 and GSK-3 act synergistically to promote the phosphatidylinositol-3 kinase (PI3K) pathway via phosphorylation of PTEN. More recent data demonstrate another mechanism through which CK2 promotes the PI3K pathway – via transcriptional regulation of PI3K pathway genes by the newly-discovered CK2-Ikaros axis. Together, these data suggest that the CK2 and GSK-3 pathways regulate AKT/PI3K signaling in leukemia via two complementary mechanisms: a) direct phosphorylation of PTEN and b) transcriptional regulation of PI3K-promoting genes. Functional interactions between CK2, Ikaros and GSK3 define a novel signaling network that regulates proliferation of leukemia cells. This regulatory network involves both direct posttranslational modifications (by CK and GSK-3) and transcriptional regulation (via CK2-mediated phosphorylation of Ikaros). This information provides a basis for the development of targeted therapy for leukemia.